1999
DOI: 10.1515/mult.1999.18.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Second language acquisition in South Tyrol: Difficulties, motivations, expectations

Abstract: Numerous publications have dealt with the issue of bilingualism in South Tyrol. However, studies have often tended to focus on one particular point of view. This paper, on the contrary, examines the topic of bilingualism and language acquisition from several perspectives highlighting some basic contradictions and shortcomings which may explain the lack of real bilingualism in the population of South Tyrol: \hepolitical-institutional aspect, within which trends in language policy are analyzed; the socio-educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…3 A more detailed analysis about the reasons for the lack of a real bilingualism in South Tyrol, viewed from political-institutional, socioeducational, and social relations perspectives, was conducted by Cavagnoli and Nardin (1999).…”
Section: Participantsmentioning
confidence: 99%
“…3 A more detailed analysis about the reasons for the lack of a real bilingualism in South Tyrol, viewed from political-institutional, socioeducational, and social relations perspectives, was conducted by Cavagnoli and Nardin (1999).…”
Section: Participantsmentioning
confidence: 99%
“…In the interviews, historical "metanarratives" and references to contemporary social/cultural contexts were frequent. This was fairly expected, since, for example, in the context of learning German in Poland (Mar-Molinero & Stevenson 2006) or South Tyrol (Cavagnoli & Nardin 1999), similar discourses are ubiquitous.…”
Section: Discussionmentioning
confidence: 86%
“…Parallel to such ventures (Pujolar & Gonzales 2013), my study concerns voluntary adult learners, which is a relatively under-researched area in general (but see Oh & Nash 2014). Studies on "new" Catalan-speakers have demonstrated that linguistic practices and language ideologies may change throughout life (Woolard 2013; for a similar case in South Tyrol, see Cavagnoli & Nardin 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MurphyLejeune 2002). However, in the general framework of learning historical languages, there have been a number of studies in the Western European context focusing on regional and autonomous settings (on learning Basque, see Azkue and Perales 2005; on learning German in South Tyrol, see Cavagnoli and Nardin 1999). So far, few attempts have been made to present the complexities of voluntary learning in East Central European contexts (but see Jaworska 2009) in general, and in the Romanian context where Hungarian is a major historical minority language in particular (but see Marton and Vincze 2011).…”
Section: Introductionmentioning
confidence: 99%